Sosialisasi Pemberian Makanan Tambahan Pada Ibu Hamil Dan Bahaya Gizi Buruk dan Stunting Di Posyandu Desa Lembeyan Kulon - Klevina, Mertisa Dwi; Mathar, Irmawati (Empowerment: Jurnal Pengabdian Masyarakat, 2024)
Nutritional status is a measure of success in fulfilling nutrition for pregnant women. Pregnant women's nutrition is nutrition that is needed in large quantities to fulfill the mother's own nutrition and the development of the fetus she is carrying. Food needs are seen not only in the portion eaten but must be determined by the quality of the nutrients contained in the food consumed. The nutritional status of the mother before pregnancy has a significant influence on the incidence of LBW. Mothers with poor nutritional status before pregnancy have a 4.27 times risk of giving birth to LBW babies compared to mothers who have good (normal) nutritional status. The aim of this activity is to measure the concern of the residents of Lembeyan Kulon Village, Lembeyan District towards the importance of Balanced Nutrition for Pregnant Women. And prevent stunting in Lembeyan Kulon Village, Lembeyan District. Raise awareness in the Lembeyan Kulon Village community regarding the importance of balanced nutrition for pregnant women.The method used is in the form of posters and demonstrations using the lecture method.